2010
DOI: 10.1016/j.pec.2009.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Patient's need for choice and information across the interface between primary and secondary care: A survey

Abstract: Care providers should take differences into account concerning patients' need for information on their illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…164,262,271 Two studies reported an association between being more educated and being more likely to be referred. 164,262 and one study reported no association.…”
Section: Patient Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…164,262,271 Two studies reported an association between being more educated and being more likely to be referred. 164,262 and one study reported no association.…”
Section: Patient Factorsmentioning
confidence: 99%
“…164,262,271 Two studies reported an association between being more educated and being more likely to be referred. 164,262 and one study reported no association. 271 The third of these studies 271 was at higher risk of bias and the evidence was graded as conflicting.…”
Section: Patient Factorsmentioning
confidence: 99%
“…Recent research has highlighted a number of areas which are key to understanding effective risk communication, such as the nature and quality of information provided to patients and health-care workers (20), patients’ and the general public’s perceived information needs (21, 22), and role of the media (23). However, little research has been carried out into the impact of institutional arrangements on specific communication strategies (24).…”
Section: Introductionmentioning
confidence: 99%
“…The health care sector is one of the public sector areas where the introduction of governance -tools has been very important in countries following the Beveridge-model, like England [19], Denmark and Sweden [20], and to a lesser degree in some countries with health care organized in accordance with the Bismarck-model, like France, Germany and the Netherlands [21,22]. …”
Section: Introductionmentioning
confidence: 99%